The Zulliger-CS in Elderly on Hemodialysis and the Relationship Between External Variables - Gregoleti, Viviane; Scortegagna, Silvana Alba (Paidéia (Ribeirão Preto), 2017)
The use of reliable instruments is an ethical condition to exert psychological evaluation. The aim of the study was to investigate the validity of the Zulliger test in the evaluation of elderly with chronic kidney disease (CKD) with focus on cognitive constructs and interpersonal relationshipsof elderly with Chronic Kidney Disease; and investigate the relationship with external variables. The 60 participants, 30 from the Clinical Group (CG) and 30 from the Non-Clinical Group (NCG), answered a socio-demographic protocol, the Mini-Mental State Examination and the Zulligertest in the Comprehensive System. The CG presented decrease of variables Xu% (p = .031,d = .58), R (p = .002,d = .78), Fd (p = .021,d = .65) and isolation (p = .006,d = .61), rise in X-%, and PHR>;GHR. There was a positive association between time since diagnosis and family support (rho = .403,p = .027). Findings confirm the relevance of the Zulligertest and family support as a health potentiator.